Marketing Innovative Policy at Meat Food Market (Economics and region, 2018)
The direction of meat processing enterprises adaptation to market environment as formation and realization of rational commodity innovation policy is defined. The enterprises innovative marketing as well as practical application of theoretical knowledge is investigated. On the basis of regional meat products market it is suggested to expand the product range at “Hlobyno Meat processing factory” LTD with “Ham with porcini mushrooms” perspective products which can obtain its market share. Two possible concepts of the product are studied. Complex integral estimation of two products variants are carried out, specifying their advantages in “meat specialty products” segment positioning. The necessity of developing and analyzing a few product concepts and its positioning at different market segments was proved.
Keywords: marketing innovation; meat processing enterprise; product policy; product concept